2017
DOI: 10.1007/s00221-017-4938-z
|View full text |Cite
|
Sign up to set email alerts
|

Interference between a fast-paced spatial puzzle task and verbal memory demands

Abstract: Research continues to provide evidence that people are poor multi-taskers. Cognitive resource theory is a common explanation for the inability to efficiently perform multiple tasks at the same time. This theory proposes that one's limited supply of cognitive resources can be utilized faster than it is replenished, which results in a performance decline, particularly when these limited resources must be allocated among multiple tasks. Researchers have proposed both domain-specific, for example, spatial versus v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…dual-task interference; Helton & Russell, 2015;Helton & Warm, 2008;Parasuraman & Mouloua, 1987;Warm et al, 2008). Many studies have demonstrated worse performance in dual-compared to single-task conditions, regardless of the type of tasks used (Blakely, Kemp, & Helton, 2016;Bourke, 1996;Darling & Helton, 2014;Epling, Blakely, Russell, & Helton, 2017Green & Helton, 2011;Head, Russell, Dorahy, Neumann, & Helton, 2012).…”
Section: Is Semantic Vigilance Impaired By Narrative Memory Demands? mentioning
confidence: 99%
See 1 more Smart Citation
“…dual-task interference; Helton & Russell, 2015;Helton & Warm, 2008;Parasuraman & Mouloua, 1987;Warm et al, 2008). Many studies have demonstrated worse performance in dual-compared to single-task conditions, regardless of the type of tasks used (Blakely, Kemp, & Helton, 2016;Bourke, 1996;Darling & Helton, 2014;Epling, Blakely, Russell, & Helton, 2017Green & Helton, 2011;Head, Russell, Dorahy, Neumann, & Helton, 2012).…”
Section: Is Semantic Vigilance Impaired By Narrative Memory Demands? mentioning
confidence: 99%
“…In addition to the decline in performance with time on task as resource stores are drained, when limited resources are distributed among more than one task, they may be utilized faster than they are replenished, resulting in further reduction in performance (i.e., dual-task interference; Helton & Russell, 2015; Helton & Warm, 2008; Parasuraman & Mouloua, 1987; Warm et al, 2008). Many studies have demonstrated worse performance in dual- compared to single-task conditions, regardless of the type of tasks used (Blakely, Kemp, & Helton, 2016; Bourke, 1996; Darling & Helton, 2014; Epling, Blakely, Russell, & Helton, 2016, 2017; Epling, Russell, & Helton, 2016; Green & Helton, 2011; Head, Helton, Russell, & Neumann, 2012; Head, Russell, Dorahy, Neumann, & Helton, 2012).…”
mentioning
confidence: 99%
“…Rock-climbing requires equilibrating and moving the entire body along routes across walls, boulders, and cliffs, using quadrupedal locomotion. It requires many physical (Baláš, 2017), psychological (Sanchez, 2017), technical (Baláš et al, 2014;Quaine, Martin, Leroux, Blanchi, & Allard, 1996), and cognitive skills (Bourdin, Teasdale, & Nougier, 1998;Epling, Blakely, Russel, & Helton, 2017). These include the crucial capacities to exert strong fingertip forces on the holds and pull ups with the upper limbs to reach the next hold (Draper, Dickson, Blackwell, Priestley, Fryer, Marshall, Shearman, Hamlin, Winter & Ellis, 2011;Watts, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…We calculated the dual-task effects, Cohen’s d z , on both tasks, and to put this in context, we combined this with the effects found in previous studies pairing the word-recall task with other tasks including a visual semantic discrimination task (Epling, Russell, & Helton, 2016), running over a flat grass track (Epling, Blakely, et al, 2016), the Sustained Attention to Response Task (SART; Head & Helton, 2014), Quadra, a game like Tetris (Epling et al, 2017), and climbing a traverse on a climbing wall (Green et al, 2014; Green & Helton, 2011). These effects are displayed in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…The single-task word recall required participants to sit on the pool’s edge with their legs in the water and listen to a list of 20 words that they would be asked to recall later. The words used in the word lists were from a previous study (Green & Helton, 2011; see supplementary materials) and have been used in numerous studies (Epling, Blakely, et al, 2016; Epling, Blakely, Russell, & Helton, 2017; Epling, Russell, & Helton, 2016; Head & Helton, 2014). One list was assigned at random to the single-task and dual-task conditions, as no study had ever found any word list differences in memorability; the lists were developed to be equally memorable.…”
Section: Methodsmentioning
confidence: 99%